The interpretation and application of ACE Tools in Singapore MRO - Tay, Su Khee (2009)
The use of Achieving Competitive Excellence (ACE) Tools in Pratt & Whitney has been widely regarded as the key to guiding Pratt & Whitney to market leader’s position. ACE is taught to all employees as a toolbox where different tools can be used to solve various problems or issues encountered during our daily work. It is also the way in which Pratt & Whitney should conduct its business. While the essence of the tools is the same, it is the interpretation and acceptance of the tools at various Maintenance Repair and Overhaul (MRO) units that prompted this study. The objective of this study is to look into the interpretation and application of ACE Tools in MRO units operating in Singapore. It will look at the implementation of ACE Tools by these units and discuss the results associated with the change brought about by the ACE Tools. In addition, it will also look into the acceptance level of the use of ACE Tools in the MRO units and whether there is any relationship between acceptance level and the level of success.